Online Alternative Media and Their Effort to Overcome News Desert in Indonesia - Astuti, Irawati Diah; Irwansyah, Irwansyah (Jurnal Komunikasi, 2022)
The development of technology and the communication industry has caused drastic changes in the media industry, especially print media. A great number of newspapers and magazines stopped printing because it was difficult to compete with online media. Therefore, the term “news desert” appears to refer to a community or area that is not covered by newspapers due to the declining population of local newspapers in various regions. The community or region seems to have disappeared from the public eye. Important issues, problems, and aspirations of residents in the region are no longer heard and their existence seems to be no longer essential. This is certainly troubling, especially regarding the function of the media as the fourth estate in democracy. However, in various regions, online alternative media are now emerging that only focus on local issues, especially issues that are not or rarely touched by mainstream media. This study aims to find out how online alternative media try to overcome the phenomenon of news desert in Indonesia. The research was conducted by case study approach with two sources of information for data collection. The first one is manual observation on two online alternative media Bandung Bergerak and Bale Bengong and the second one is interviews with the Editor-in-Chief of the two media. Based on this research, several results were obtained, 1) alternative media report news about local communities that are rarely presented in the mainstream media and causing news desert, 2) an in-depth data-based journalism approach and citizen journalism in alternative media are capable of uniting local communities and communities, 3) news that does not rely on clickbait or the latest updates in online alternative media can be enjoyed without expiration,  and 4) the proximity of online alternative media to the society is one of the leading strategies for overcoming the news desert.